THE IMPACT OF MOBILE HEALTH ON HEALTHY LIFESTYLE COMPLIANCE AND QUALITY OF LIFE OF DIABETES MELLITUS PATIENTS: A SCOPING REVIEW - Santosa, Winanda Rizki Bagus; Sujatmiko, Sujatmiko; Astutik, Wahyu Sri; Manohara, Galuh Dharanindya Ica; Nuraini, Ida Rizqa (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Compliance with a healthy lifestyle and improving the quality of life of patients can be done through education with mobile health to prevent long-term complications in Diabetes Mellitus (DM) patients. Aims of the research this is to know the impact of mobile health on healthy lifestyle compliance and the quality of life of DM patients. In this research, these are PubMed, CINAHL, and Scopus. The search review uses the keywords "Diabetes Mellitus," "Mobile Health," "Healthy Lifestyle Compliance," and "Quality of Life" in the articles. Based on the results, 12 out of 305 articles were identified as feasible. Analysis showed that mobile health can be used for improving healthy lifestyle compliance, and improving the quality of life among DM patients. The time DM patients used mobile health application for education varies greatly. Mobile health has great potential to help improve compliance with lifestyle health, and quality of life for DM patients.